Uporaba termotesta - Meh, Duška (Medicinski razgledi, 2002)
Modern neurophysiological methods (including the accurate psychophysical Marstock method) were used to determine sensitivity to heat, cold, and pain due to heat and cold (specific thermal and pain sensitivity) in six groups of patients suffering from various diseases (type 1 and type 2 diabetes mellitus,primary Sjogren's syndrome, peripheral neuropathy of various etiologies, syringomyelia and multiple sclerosis). Various types of abnormalities were found, but no specific alteration patterns were identified.The abnormalities recorded depended upon the stage of the disease. The study confirms that thermotest is a sensitive, although unfortunately unspecific, index of somatoesthesia. The method is appropriate for following the disease or its progression during rehabilitation. For an exact diagnosis of somatosensory dysfunction, aberrant sensations are at least as important ashypo- or hyperesthetic phenomena.
Keywords: Bolečinski prag; Temperature Sense; Pain Threshold; Multipla skleroza; Diabetes Mellitus; Sjoegrenov sindrom; Sjogren'S Syndrome; Sladkorna bolezen; Temperaturni čut; Multiple Sclerosis; Periferno živčevje, bolezni; Peripheral Nervous System Diseases; nevrofiziologija; fiziologija; živčevje; bolniki; občutljivost; motnje